Impact of rule changes on tactical performance: a comparative analysis of attacking and defensive metrics in the UEFA Champions League - Che Ab Lah, Che Ameer Aqeel; Sabariman, Hazim Muhaimin; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Adnan, Mohd Aizzat; Abu Kasim, Nurul Ain; Raja Hussain, Raja Nurul Jannat (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study examines how the shift from the traditional to the revised UEFA Champions League format influenced the tactical approaches of the competition's top four teams. By comparing performance metrics between the 2023/2024 and 2024/2025 seasons, the research identifies shifts in attacking and defensive strategies prompted by these structural changes. Ultimately, the findings highlight how elite clubs adapt to evolving competition designs, offering critical insights for performance analytics, coaching preparation, and high-stakes organizational decision-making.